Is Salvage Liver Resection Necessary for Initially Unresectable Hepatocellular Carcinoma Patients Downstaged by Transarterial Chemoembolization? Ten Years of Experience. (2nd August 2016) - Zhang, Yingqiang; Huang, Guihua; Wang, Yu; Liang, Lijian; Peng, Baogang; Fan, Wenzhe; Yang, Jianyong; Huang, Yonghui; Yao, Wang; Li, Jiaping
Abstract : Introduction: This study evaluated long-term outcomes of salvage surgery as additional therapy following downstaging of hepatocellular carcinoma (HCC) with transarterial chemoembolization (TACE) in patients with initially unresectable HCC. Methods: A retrospective analysis was performed of 831 consecutive patients with unresectable HCC who underwent TACE as initial treatment between June 2004 and December 2014. Of these, 82 patients with downstaged resectable HCC were enrolled in this study: 43 received salvage surgery (S group) and the remaining 39, who refused salvage resection, were the control group (T group). The primary endpoint was overall survival (OS). Results: The median OS in the S and T groups was 49 and 31 months, respectively ( p = .027). The 2-, 4-, and 5-year survival rates were 93%, 47%, and 26% in the S group and 74%, 18%, and 10% in the T group, respectively ( p = .019). Treatment modality (hazard ratio [HR], 0.337; 95% confidential interval [CI], 0.184–0.616; p < .001) and response to TACE (complete vs. partial; HR, 3.154; 95% CI, 1.709–5.822; p < .001) were independent prognostic factors for survival. The median OS for patients in the complete response and partial response (PR) subgroups was 50 and 49 months, respectively, in the S group and 54 and 24 months, respectively, in the T group ( p = .699 and p < .001, respectively). The median OS for HCC patients with macroscopic vascular invasion (MVI) was 58 and 30 months in the S and T groups, respectively ( p = .024). Conclusion: Salvage surgery after downstaging of unresectable HCC had a survival benefit only for patients with MVI or a PR to TACE. Abstract : After downstaging of hepatocellular carcinoma (HCC) with transarterial chemoembolization (TACE) in patients with initially unresectable HCC, long-term outcomes of salvage surgery as additional therapy were evaluated. Treatment method and response to TACE were independent prognostic factors for survival. Salvage surgery after downstaging of unresectable HCC had a survival benefit only for patients with macroscopic vascular invasion or a partial response to TACE.